Semen quality of caged red jungle, serama and village fowls and effects of dietary energy and protein on semen quality of caged red jungle fowl - Ismail, Fazhana (2013)
The primary objective of this research were to compare semen quality in three local chicken breeds; Red Jungle Fowl (RJF), Serama (SC) and village chicken(VC) and semen production and fertility of caged Red Jungle Fowl (RJF) related to the dietary energy and protein level. Semen quality was compared on 8 cockerels of each breeds aged 28 weeks to achieve the first objective. In second experiment, a total of 45 RJF cockerels aged 24 weeks fed on five different dietary energy and protein level accordingly to determine its effects on their semen quality and fertility. The collection of semen was carried out using the manual abdominal massage once a week from each individual cockerel. Spermatozoa were screened for the volume,concentration, color, size and the percentage of live, motility, total abnormal and morphological defects spermatozoa. When at least 80% of the hen started consistently laying eggs, the artificial insemination was done in each hen. Fertility was determined by two methods; Semen Quality Factor (SQF) calculation and percentage of fertile eggs. Total feed intake and weight gain percentage were also recorded. Statistical analyses of the data were done using one way analysis of variance (ANOVA) in the statistical programme SPSS version 17.0. The results of the study indicate that different breeds of chicken significantly produced different spermatozoa characteristics. All three breeds produced more than 90% of live spermatozoa which indicated a good quality of fresh semen. SC produced lowest semen volume (0.14ml) and concentration (1.78x 109 sperms/ml) with least motile spermatozoa percentage (49%) and highest abnormal spermatozoa (34.5%) were observed. VC and RJF were not significantly different in semen volume but RJF was significantly produced higher semen concentration (4.51 x 109 sperms/ml) with high motile spermatozoa (53.8%). In addition, RJF significantly produced lower abnormal spermatozoa (26.7%) compared to VC (28.1%). Since RJF semen characteristics was the most superior compared to SR and VC, only RJF cockerels were selected to be used in dietary effects on semen quality experiment assuming that the affects would be more obviousl determined. Five diet treatments were determined; Group A, control (3000kcal/kg ME and 16% CP), Group B (3320kcal/kg ME and 16% CP),Group C (2621kcal/kg ME and 16% CP, Group D (2980kcal/kg ME and 20% CP) and Group E (3000kcal/kg ME and 10% CP). It was found that providing higher dietary energy significantly reduced semen volume (0.27ml) and concentration (4.08 x 109 sperms/ml) in RJF but improved the percentage of general sperm motility (68.4%) and live spermatozoa (97.15%). Lower dietary energy did not detriment to the semen volume (0.33ml) but significantly reduced the semen concentration (4.00 x 109 sperms/ml), sperm general motility (47.3%), live spermatozoa (92.11%) and total abnormalities (24.34%). Higher dietary protein significantly reduced semen volume (0.26ml),concentration (4.22 x 109 sperms/ml), and live spermatozoa (85.31%). It was also caused significantly increased total abnormalities (26.93%). Lower dietary protein at 10% significantly reduced semen volume (0.25ml),concentration (3.78 x 109 sperms/ml), general motility (51.3%) ,live spermatozoa(58.16%) and total abnormalities(25.71%). SQF and fertile eggs percentage were significantly affected in all diet treatments. SQF in Group B,C, D and E were 8.03, 9.99, 8.02 and 7.02, respectively which were significantly lower than control group, 10.86. Fertile eggs percentage was 79.1%, 83.4%, 72.8% and 59.8% in Group B, C, D and E , respectively which was also lower than control group, 85.8%. From this study, RJF produced the greatest quality of semen compared to SC and VC. Providing too high or too low dietary energy or protein levels may detriment to semen quality and fertility in caged RJF. Therefore,recommended dietary energy at 3000 kcal ME/kg and 16% crude protein should be followed so that the optimum productivity will be maintained. SQF could be one of the methods to predict fertility in breeder males during parentstock selection.